EDITORIAL | REDAKTORIAUS ŽODIS - Mačianskienė, Nemira` (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
The initial idea to undertake the mission of providing a platform for research on multilingualism arose from constant discussions of language teachers and researchers on language teaching and learning issues, sharing long-term experience accumulated at VMU in language policy area since its re-establishment in 1989. The idea was enhanced in the international conferences organized by the IFL, presenting conclusions of the ongoing research into students’ plurilingual competence development enhancing multilingualism in a previously monolingual higher education space in Lithuania, which has been increasingly developing into a multilingual and multicultural learning space for the last decade.